EVALUASI DAN STUDI PERSEPSI TERHADAP TINGKAT PELAYANAN JALUR PEJALAN KAKI KAWASAN PENDIDIKAN - Nurul Adhaini; Yossyafra Yossyafra; Purnawan Purnawan (Rang Teknik Journal, 2020)
Ade Irma Suryani street is one of the area in Payakumbuh city that is designed as an area which mainly function as educational and others such as offices and health service area. Educational infrastructure on this street includes Public Primary School 04 Payakumbuh, Raudhatul Jannah Payakumbuh Islamic Middle School, Campus II Andalas University Payakumbuh and PAUD Bakti Pediatrics. Educational, offices and health service infrastructure encourage the society to use the pedestrian pathways. The existing condition of infrastructure and facilities are still considered inadequate with various problems. This research aim to evaluate the level of service of pedestrian pathways, to review public perception of pedestrian pathways service, and to set the primary variable for the enhancement of pedestrian pathways based on user perception. The quotation of the level of pedestrian service is based on Minister of Public Works Regulation Number: 03/PRT/M/2014. Characteristic analysis result stated that the level of service on the north side is regarded as “A”. While the level of service on the south side is regarded as “B”. Public perception analysis of pedestrian pathways service is carried using the Importance Performance Analysis (IPA) method, with 6 research variable namely accessibility, safety, comfort, aestethic, convenience and social interactions. The result of the analysis stated that the primary priorities are accessibilty, aesthetic, convenience and social interactions, the variable which need maintance in it’s performance is safety and the variable which considered excessive is comfort.